2016
DOI: 10.1016/j.ekir.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Autologous Selected Renal Cells in Diabetic Chronic Kidney Disease Stages 3 and 4—Clinical Experience of a “First in Human” Study

Abstract: IntroductionAnimal models of chronic kidney disease demonstrate that a redundant population of therapeutically bioactive selected renal cells (SRCs) can be delivered to the kidney through intraparenchymal injection and arrest disease progression. Direct injection of SRCs has been shown to attenuate nuclear factor−κB, which is known to drive tissue inflammation, as well as the transforming growth factor−β−mediated plasminogen activator inhibitor−1 response that drives tissue fibrosis.MethodsWe present experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…This transplantation had been carried out within the framework of a larger study on the potentially beneficial effects of autologous stem cell transplantation in kidneys in patients with type 2 diabetic chronic kidney disease stage III-IV, where renal volume change was one of the outcomes. The overall outcome of the autologous transplantation study has been published elsewhere ( 7 ). A total of 200 kidney image stacks were thus processed.…”
Section: Methodsmentioning
confidence: 99%
“…This transplantation had been carried out within the framework of a larger study on the potentially beneficial effects of autologous stem cell transplantation in kidneys in patients with type 2 diabetic chronic kidney disease stage III-IV, where renal volume change was one of the outcomes. The overall outcome of the autologous transplantation study has been published elsewhere ( 7 ). A total of 200 kidney image stacks were thus processed.…”
Section: Methodsmentioning
confidence: 99%
“…While most of the secretome studies have focused on MSC as a source of secretome, several studies have reported that different types of therapeutic cells could be used as secretome sources. As noted above, primary renal cells demonstrated therapeutic effects on the improvement of renal functions 4,5,52) . Dominguez et al showed the therapeutic effects of primary renal cell-derived secretome on kidney improvement 53) .…”
Section: Secretome Derived From Other Cell Typesmentioning
confidence: 78%
“…A commonly used approach in cell-based therapy is cell transplantation, where therapeutic cells are exogenously administered to achieve the repair. The cell transplantation approach using various cell types have resulted in reno-therapeutic outcomes in many pre-clinical [1][2][3] and clinical studies 4) . For example, primary renal cells isolated from kidney tissues were introduced to improve renal functions from kidney diseases in a pre-clinical 5) and clinical study 4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This current trial uses a percutaneous, image-guided techniques with conscious sedation. The phase I trial of high-risk CKD diabetics who were injected with RE-ACT used a laparoscopically assisted surgical approach and general anesthesia [18]. Furthermore, the cellbased therapeutic could be administered (mean eGFR <30 mL/min) safely in a small cohort [17].…”
Section: Discussionmentioning
confidence: 99%